Abenteuer am Golf: Saudi-Arabiens Wandel unter den Salmans - Bohn, Miriam; Vollmann, Erik; Zumbrägel, Tobias (Gegenwartskunde: Zeitschrift für Gesellschaft, Wirtschaft, Politik und Bildung, 2018)

Decentralisation as Authoritarian Upgrading? Evidence from Jordan and Morocco - Vollmann, Erik; Bohn, Miriam; Sturm, Roland; Demmelhuber, Thomas (Journal of North African Studies, 2020)
A vivid regional and international debate on the significance of local politics and the respective actors came back to life after the Arab uprisings in 2011, which initiated decentralisation reforms in several MENA countries. Decentralisation advocates expect the reforms to foster democratisation, local autonomy and the overall socioeconomic situation, but Middle Eastern regimes also engage in decentralisation reforms for the sake of their own durability. This article assesses the potential of decentralisation reforms to develop mechanisms that contribute to authoritarian upgrading. We systematically include subnational politics and dynamics, as they are essential for deepening our understanding of the potential for reforms to uphold non-democratic regimes. Decentralisation is a promising test case, as the delegation of power away from the centre towards subnational actors and institutions affects the regime’s ability to control the polity. In our analysis, we focus on three salient aspects that influence the outcome of a decentralisation reform: (1) the legal outline of decentralisation, (2) its financial organisation as well as (3) the management of central, regional, and local elite networks. Subnational authoritarian upgrading via decentralisation reforms in Jordan and Morocco seem to focus on the satisfaction and containment of civil society as well as on the management and control of elites and oppositional actors.<br

Dezentralisierung in der arabischen Welt: ein konzeptioneller Zugang - Bohn, Miriam; Demmelhuber, Thomas; Sturm, Roland; Vollmann, Erik (Jahrbuch des Föderalismus 2018, 2018)

The Dynamics of Decentralization in the MENA: Processes, Outcomes, and Obstacles - Shalaby, Marwa; Weiss, Chagai; Lust, Ellen; Kao, Kristen; Vollmann, Erik; Bergh, Sylvia; Karmel, Ezra; Bohn, Miriam; Kherigi, Intissar; Kadirbeyoglu, Zeynep (Social Science Research Network, 2020)
This working paper is part of a two-year project on decentralization in the MENA, focusing on Oman. The broader project aims to make three main contributions. First, it seeks to promote policy-relevant, scholarly research on decentralization, and pave the way for further cross-national studies and analyses on the topic. Second, it will inform stakeholders in the Sultanate of Oman, focusing on how differences in community governance structures –i.e. the extent to which citizens turn to state institutions versus non-state actors for services and participate in decision processes –affect challenges todecentralization. Third, it aims to strengthen and expand networks of scholars and other decentralization-oriented stakeholders from around the world, whilst also engaging local voices. To achieve these objectives, the study employs a multi-method approach to explore how and when citizens turn to state and non-state institutions. The goal is not only to expand our understanding of decentralization in the contextof strong social institutions, but also to establish sustainable scholarly and policy-relevant networks and dialogues around these issues. In March 2020, we brought together decentralization scholars from around the MENA region at the University of Gothenburg. The discussions focused around the design of decentralization reforms, obstacles, progress and outcomes. It also highlighted the goals and design of upcoming research on decentralization in Oman. Furthermore, participants discussed project design and potential points of comparison with on-going research in other MENA countries. The following compendium is the result of that two-day workshop
Keywords: Decentralization; Tunisia; Jordan; Morocco; Turkey